Beyond Legalism: Reframing Maqāṣid al-Sharīʿah for Value-Based Impact in Contemporary Islamic Finance - Widayanti, Ipuk (Journal of Family and Sharia, 2026)
The rapid growth of Islamic finance has been accompanied by increasing concerns over its tendency toward formalistic legal compliance, often prioritizing contractual validity over substantive socio-economic impact. This study seeks to critically examine the prevailing legalistic orientation and to reframe the role of maqāṣid al-sharīʿah as a foundational framework for value-based impact in contemporary Islamic finance. While maqāṣid al-sharīʿah has long been recognized as the higher objectives of Islamic law, its operationalization within financial practices remains limited and frequently reduced to symbolic justification rather than substantive guidance. This research adopts a qualitative and conceptual approach, combining normative analysis of classical Islamic jurisprudence with contemporary socio-economic and financial discourse. It explores how maqāṣid al-sharīʿah—particularly the principles of justice (ʿadl), welfare (maṣlaḥah), and prevention of harm (ḍarar)—can be reinterpreted to address current challenges such as financial inclusion, ethical investment, and social equity. The findings reveal a significant gap between the theoretical ideals of maqāṣid and their practical implementation, largely due to institutional inertia, regulatory limitations, and the dominance of risk-averse, compliance-driven models. Furthermore, the study proposes a shift from a rule-based paradigm to a value-based framework that emphasizes impact-oriented finance. This transformation requires integrating maqāṣid into governance structures, product development, and performance measurement, thereby aligning financial activities with broader socio-economic objectives. The paper argues that such a reframing is essential to enhance the credibility, sustainability, and transformative potential of Islamic finance in the global financial system.